2005
DOI: 10.1177/154405910508400407
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid-hormone-related Protein Induces Expression of Receptor Activator of NF-κB Ligand in Human Periodontal Ligament Cells via a cAMP/Protein Kinase A-independent Pathway

Abstract: PTHrP, parathyroid-hormone-related protein; TGF-beta, transforming growth factor-beta; EGF, epidermal growth factor; RANKL, receptor activator of NF-kappaB ligand; OPG, osteoprotegerin; PDL, periodontal ligament; TRAP, tartrate-resistant acid phosphatase; PKA, protein kinase A; PKC, protein kinase C; MAP, mitogen-activated protein; ERK, extracellular signal-regulated kinase; cAMP, cyclic Adenosine 3'5'-Monophosphate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 34 publications
(39 reference statements)
1
33
0
2
Order By: Relevance
“…PTHLH stimulates osteoclastogenesis by inducing tartrate-resistant acidic phosphatase in PDL cells, while increasing the receptor activator of the NF-κB ligand and decreasing osteoprotegerin levels (Fukushima et al 2005). PTHLH represses BSP, osteocalcin, and the mineralization in PDL cells and, potentially, in cementoblasts Ouyang et al 2000a,b).…”
Section: Other Peptide Hormonesmentioning
confidence: 99%
“…PTHLH stimulates osteoclastogenesis by inducing tartrate-resistant acidic phosphatase in PDL cells, while increasing the receptor activator of the NF-κB ligand and decreasing osteoprotegerin levels (Fukushima et al 2005). PTHLH represses BSP, osteocalcin, and the mineralization in PDL cells and, potentially, in cementoblasts Ouyang et al 2000a,b).…”
Section: Other Peptide Hormonesmentioning
confidence: 99%
“…The infl ammatory mediators, such as interleukin (IL)-1 and prostaglandin E 2 (PGE 2 ), induce RANKL expression leading ultimately to alveolar bone loss [3,4] . Studies have demonstrated the expression of RANKL in periodontal tissue and periodontal ligament cells [5][6][7] .…”
mentioning
confidence: 99%
“…31 Moreover, coculture of human PDLCs and mouse spleen cells also induced mature osteoclasts. 32 In our study, the conditioned media from the intervening human PDLCs were used to coculture OBs and pre-OCs derived from the rat and successfully produce mature OCs. It further strengthened the previously reported crosstalk between proteins derived from humans and those derived from rodents.…”
Section: Discussionmentioning
confidence: 99%